PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL BERBASIS AUGMENTED REALITY (AR) TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VI SDI AL - IKHLAS KARANGREJO TULUNGAGUNG - Jelita Usmatul Nur Hidaningrum; Aditya Pringga Satria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the learning process at SDI Al-Ikhlas Karangrejo, which had not yet implemented digital learning media based on augmented reality (AR). The instructional methods used were still conventional and lacked the integration of interactive media that could facilitate students' visual understanding. The purpose of this study was to examine the effect of using AR-based digital learning media on students’ mathematics learning outcomes at SDI Al-Ikhlas Karangrejo. This research employed a quantitative approach with a quasi-experimental design using a non-equivalent control group. The sample consisted of all sixth-grade students, totaling 50 participants. Data were collected through tests that had been validated for accuracy. Data analysis included normality testing, homogeneity testing, and hypothesis testing using the independent sample t-test. The findings revealed that the experimental group, which used AR media, achieved a higher average gain score of 42.5, compared to the control group's gain score of 20.4. The t-test results showed a significance level of p < 0.05, indicating a positive and significant effect of AR media use on students’ mathematics learning outcomes. This study supports the integration of augmented reality technology as an effective instructional strategy to enhance learning outcomes at the elementary school level.